2020
DOI: 10.1101/2020.07.01.20144386
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical characterization of respiratory droplet production during common airway procedures using high-speed imaging

Abstract: Background: During the COVID-19 pandemic, a significant number of healthcare workers have been infected with SARS-CoV-2. However, there remains little knowledge regarding droplet dissemination during airway management procedures in real life settings. Methods: 12 different airway management procedures were investigated during routine clinical care. A high-speed video camera (1000 frames/second) was for imaging. Quantitative droplet characteristics as size, distance traveled, and velocity were computed… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…One was included. (44) In addition, we reviewed LitCOVID and found no additional studies. We reviewed the collection of 474 articles on COVID-19 within the Chinese Medical Journal Network, screened 4 articles at full text, and included none.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One was included. (44) In addition, we reviewed LitCOVID and found no additional studies. We reviewed the collection of 474 articles on COVID-19 within the Chinese Medical Journal Network, screened 4 articles at full text, and included none.…”
Section: Resultsmentioning
confidence: 99%
“…A second experimental study, identified through a preprint server, sought to characterize the pattern of droplet dispersion with human participants of unknown clinical status receiving selected common airway management procedures during routine care, one of which was nebulization. (44) Droplet patterns were captured by a high-speed camera of illuminated droplets against a black background. They found no evidence of droplet dispersion during nebulization, though they noted that fine aerosols were detected but not quantified due to ''abundance.…”
Section: Risk Of Transmitting Covid-19mentioning
confidence: 99%
“…The realistic coughing velocity profile of Gupta et al [46] is scaled to the maximum total velocity of 26.4 m s taken from the experiments of Müller et al [15], see Fig. 2.…”
Section: Profiles Of the Inlet Boundaries (Continuous Phase)mentioning
confidence: 99%
“…Other authors distinguish between liquid particles suspended in the air that remain in the air for a short time due to ballistic trajectories (droplets) and particles that float and remain in the air for a longer time (aerosol particles). In this study, based on previous results of our group (clinical characterization), we will use the second definition based on ballistic and hovering behavior of respiratory particles [15]. Filtering mechanisms in the upper airways effectively seems to remove the majority of particles larger than 5 µm from the air stream already in the nose/mouth/throat [12].…”
Section: Introductionmentioning
confidence: 99%